Trends in the prevalence of Chronic Kidney Disease in the United States, 1999–2018 - Mansi Zhuang; Mansi Zhuang; Xiaogang Lv; Yanan Zhu; Nan Zheng; Yiqiang Zhan; Yiqiang Zhan (Frontiers in Medicine)
BackgroundChronic Kidney Disease (CKD) is an escalating public health concern in the United States, linked with significant morbidity, mortality, and healthcare costs. Despite known risk factors like age, hypertension, and diabetes, comprehensive studies examining temporal trends in CKD prevalence are scarce. This study aims to analyze these trends using data from the National Health and Nutrition Examination Survey (NHANES).MethodsThis cross-sectional study analyzed NHANES data spanning 20 years (1999–2018), including 55,081 adults aged 20 years and above. Key renal function indicators like estimated glomerular filtration rate (eGFR) and albumin-to-creatinine ratio (ACR) were assessed, and CKD stages were categorized accordingly.ResultsA fluctuating trend in CKD prevalence was observed, with early CKD stages (G1–G3) increasing from 9.28% in 1999–2000 to 12.93% in 2017–2018. Advanced CKD stages (G4–G5) showed a slight increase in prevalence from 0.3% in 1999–2000 to 0.51% in 2017–2018. Notable disparities were observed across age groups, diabetes status, and racial categories. Relatively, the elderly, women, and non-Hispanic whites have a higher prevalence of CKD, while individuals with diabetes have a consistently higher prevalence of early CKD from 1999 to 2018. The increasing prevalence of diabetes during the study period highlights its significant role as a CKD risk factor.ConclusionThe prevalence of CKD in the U.S. has been rising over the period 1999–2018, and varying across demographic groups, underscoring significant disparities and risk factors. These insights are crucial for healthcare planning, policy formulation, and targeted interventions for CKD management.